Ejercicios aeróbicos en el sobrepeso del personal pasivo del ejército - Gavilanes Paredes, Edison Danilo (2025)
The present study consisted of a descriptive, quantitative analysis of the physical and morphological characteristics of retired military personnel of the Ecuadorian Army residing in the city of Riobamba. The purpose was to determine and assess their current body condition and to develop a proposal for an intervention program using aerobic and anaerobic exercises to improve their quality of life. The research followed a non-experimental, cross-sectional, and applied design, seeking to collect and analyze anthropometric data obtained through indicators such as body mass index (BMI) and skinfold measurements, in compliance with the standards established by the International Society for the Advancement of Kinanthropometry (ISAK) and the classifications provided by the World Health Organization (WHO). The study population consisted of 100 retired military personnel who underwent a thorough physical assessment. The results revealed that 58% of participants were overweight, 26% had normal weight, and 16% presented various degrees of obesity. These findings reflect a clear tendency toward obesity and low physical fitness. Based on the diagnostic results, a practical proposal entitled “Manual of Aerobic and Anaerobic Exercises for Retired Military Personnel” was developed. This manual is grounded in physiological principles of physical training and tailored to the assessed sample's characteristics and capabilities. It was designed as both a pedagogical and preventive tool to promote muscle strengthening, cardiovascular endurance, fat reduction, and the development of healthy lifestyle habits. In conclusion, this study's findings confirm that anthropometric assessment is an essential resource for planning adapted physical activity programs. Moreover, systematic physical training incorporating aerobic and anaerobic exercises is an effective means to combat overweight, improve overall health, and encourage active and healthy aging among retired military personnel. Institutionally, it is recommended that permanent physical education programs be implemented, incorporating anthropometric monitoring and nutritional counseling into the Ecuadorian Army’s welfare policies.